THE EVALUATION OF ENGLISH COURSEBOOK CHALLENGES 1 FROM THE PERSPECTIVES OF TEACHERS - Wawan Setiawan (Universitas Wiralodra, 2023)
This research aimed to investigate teachers’ perspectives on the suitability of the English coursebook Challenges 1 and the strategies employed by the teachers at International Language Programs (ILP). Through qualitative research, it was found that the coursebook provided a balanced syllabus and guidance for teachers. It presented language skills, language content, and various topics for students. The teachers also perceived that the coursebook provide clears aims to follow. However, there were negative perspectives believed by some teachers on several items such as the coverage of speaking skills, the suitability of activities with the students’ preferred classroom activities, and the suitability of topics with students’ level. The data from interviews also indicated that the teachers adapted the materials by adding, deleting, and modifying the materials to meet their target learning needs and to make the materials more relevant to the teaching context. To some extent, it shows that the coursebook contains areas that need to be developed.